Development and validation of a self-regulation scale within the German version of the Early Development Instrument - Georg, Sabine; Genser, Bernd; Fischer, Joachim E.; Sachse, Steffi; Bock, Freia (BMC pediatrics, 2023)
Early childhood self-regulation (SR) is key for many health- and education-related outcomes across the life span. Kindergarten age is a crucial period for SR development, and within this developmental window, potential SR difficulties can still be compensated for (e.g., through interventions). However, efficient measurement of SR through brief, comprehensive, and easy-to-use instruments that identify SR difficulties are scarce. To address this need, we used items of an internationally applied kindergarten teacher questionnaire—the Early Development Instrument (EDI) - to develop and validate a specific SR measurement scale.